Two-Grid Finite Element Method for Time-Fractional Nonlinear Schrödinger Equation (Journal of Computational Mathematics, 2024)
A two-grid finite element method with $L1$ scheme is presented for solving two-dimensional time-fractional nonlinear Schrödinger equation. The finite element solution in the $L^∞$-norm are proved bounded without any time-step size conditions (dependent on spatial-step size). The classical $L1$ scheme is considered in the time direction, and the two-gridfinite element method is applied in spatial direction. The optimal order error estimationsof the two-grid solution in the $L^p$-norm is proved without any time-step size conditions.It is shown, both theoretically and numerically, that the coarse space can be extremelycoarse, with no loss in the order of accuracy.